(untitled) (Research, Society and Development, 2021)
Anxiety is conceptualized as a psychic state of apprehension or exacerbated fear instigated by anticipation of an unpleasant, dangerous or even challenging situation. The anxiety disorder is present in human development, present in all periods of life. However, there are circumstances that anxiety can be activated, such as the birth of a child, causing psychological changes, which may lead to obstetric complications, such as premature birth and low birth weight of the baby, pre-eclampsia and meconium in the amniotic fluid, increased motor activity in the fetus and depression during pregnancy. Thus, the present study aims to perform an exploratory study and literature review on anxiety disorders involving the perinatal phase. From the literature, it was found that the perinatal phase is a vulnerable period during which depression and anxiety occur. This is due to a unique combination of neurohormonal and psychosocial stressors, intensifying women’s vulnerability to depressive symptoms and anxiety disorders. Pregnancy-related anxiety symptoms have been found to be analogous to those defined for anxiety disorders. However, the behavioral consequences of pregnancy-related anxiety similarly apply uniquely to certain women and may serve as important indicators of the severity of the disorder.